In-Silico design and verification of an extracorporeal normothermic cardiac perfusion system for use during heart transplantation procedures - Van Den Berg, Ronald (Division of Biomedical Engineering, 2026)
Heart transplantation relies on effective donor organ preservation to ensure successful graft viability. Since the first human heart transplant in 1967 by Christiaan Barnard, organ preservation techniques have evolved from static cold storage with cardioplegic arrest to continuous blood perfusion, which enhances metabolic support and extends viable ischemic time. This study explores the development of a system for continuous myocardial perfusion to improve donor heart preservation during transplantation. Using in-silico modelling and simulation, the study defines functional requirements for a proof-of-concept system capable of achieving physiologically relevant pressure and flow waveforms necessary for sustained coronary perfusion. A cardiovascular hemodynamic simulation environment was established by adapting lumped parameter models and integrating computed tomography angiograms, facilitating both in-silico and coupled in-vitro validation analyses. This enabled the development of a bench testing model that replicated physiologically relevant coronary perfusion dynamics. The bench testing model provided critical insights for refining in-silico simulations and optimising design parameters for improved myocardial perfusion. Validation was performed through vessel-specific flow rate comparisons with computational fluid dynamics simulations. Experimental results identified a time delay in relation to the identified set of functional and control parameters when achieving target physiological pressures, informing future system optimisation. Further findings allowed for the identification of relative flow proportion exiting through the Left Circumflex and Right Major Coronary arteries and was shown to behave as a second order time derivative with respect to the inflow waveform applied to a fabricated flow phantom during testing. Similarly, the proportion of flow exiting through the Left Anterior Descending and Ramus Intermedius arteries exhibited first order time derivative behaviour in relation to the inflow signal. The resultant outcomes of testing and analysis allowed for the tuning of an embedded pump control system yielding the optimised parameter control values for proportional, integral and derivative gain of 147.74, 2.57 and -4974.96 respectively. The findings of this study establish a framework for the development of an automated continuous myocardial perfusion system, contributing to enhanced donor heart preservation strategies for clinical transplantation. .